Occlusion and occlusal characteristics of the primary dentition in Emirati schoolchildren - Vivek Padmanabhan; Bayan Madan; Sundus Shahid (Faculty of Dental Medicine, Universitas Airlangga https://fkg.unair.ac.id/en, 2021)
Background: The prevalence of occlusion and various occlusal characteristics differ between populations. Major contributions to these different types of occlusion and occlusal features include ethnic, genetic and environmental factors. Purpose: The objective of the study was to understand the type and prevalence of terminal plane relationships and other occlusal traits, including physiological spacing and primate spacing, in Emirati schoolchildren. Methods: A cross-sectional study was conducted involving 458 participants in the age range of 3–6 years. A clinical evaluation was performed to record other occlusal characteristics. The data was then subjected to statistical analysis. Results: The present study revealed that the bilateral flush terminal plane was seen in 40.8% of the examined children, the bilateral mesial step in 37.3% and the bilateral distal step in 1.7%. It was found that 44.5% of the examined children had physiologic space in both the upper and lower arches, while 14.19% of them had physiologic space only in the upper arch, 2.18% had it only in the lower arch, and 39% of them had no physiologic space. Primate space was found to be present in both the upper and lower arches in 46% of the examined children. Conclusions: The bilateral flush terminal plane relationship was the most common, and the bilateral distal step was the least common of the terminal plane relationships. In addition, primate spacing had a lower prevalence when compared to other studies.